Status, Stratified Rights, and Accommodation in International Relations. Issue 1 (10th May 2019) - Ward, Steven
Abstract: Denied status claims can produce serious interstate conflict and accommodation may thus be an important means of avoiding conflict with rising and reemerging status seekers such as China and Russia. But accommodation is an underdeveloped concept. This article draws on scholarship about recognition and hierarchy to propose a novel means of understanding status accommodation: as behavior that sends signals to status seekers about the validity of claims to stratified rights. This framework implies that acts that signal status denial (and thus cause conflict over status) may be driven by three broad kinds of processes: anxiety about a state's position in the world; incompatibility between nonstatus interests and claims to status-implicated rights; and fears about the implications of status accommodation for the validity of discourses and ideas that produce both international and domestic order. These dynamics—especially the latter two—may be linked to domestic political mechanisms and concerns in ways that analysts do not fully appreciate. I illustrate the framework by examining the forces that drove the United States to deny Japanese claims to equal status during the decades before World War II.